Detection of interleukin-6 and interleukin-8 in serum from women with recurrent spontaneous abortion - Baghdad Science Journal (مجلة بغداد للعلوم)
To investigate the role of IL-6 and IL-8 in the immune-regulatory mechanisms involved in the recurrent spontaneous abortion of the first trimester of pregnancy. Serum level of IL-6 and IL-8 were determined in 25 women of age (20-35) years who had a spontaneous abortion of unknown aetiology during the first trimester of pregnancy .They were compared with the corresponding levels of 20 pregnant and non-pregnant women as control groups .cytokine levels were measured by (ELISA) technique .The women with spontaneous abortion had highly significant (P < 0.01) increased serum level of IL-8 and highly significant (P < 0.01 ) decreased level of IL-6 compared to those with normal pregnant and non-pregnant women. The results of this study may be related to the underlying aetiopathogenetic mechanisms , however , There is sufficient evidence for their use as predictive markers of pregnancy outcome.